Improving the Pedagogical Competence of Central Java Province History Teachers Through Quizizz Media-Based Edutainment Method Guidance - Suryadi, Andy; Atno, Atno; Kurniawan, Ganda Febri (CV. Rayyan Dwi Bharata, 2024)
The integration of technology in history learning is very important, but teaching techniques and competence in developing enjoyable learning situations are no less important. The problem that has been identified is that history teachers in Central Java Province are not familiar with edutainment in concept or practice. This is a challenge for the Service Team to be able to resolve this problem. Quizizz media-based edutainment is a means of creating an interactive and creative learning atmosphere. Technically, the implementation of quizizz media-based edutainment training activities for AGSI Central Java Province is as follows: Preparation. This preparation stage is carried out to analyze the problem in more depth and formulate strategic steps in resolving the problem. Implementation of Activities. Preparing a guidebook on implementing quizizz media-based edutainment. Preparing a hotline that provides consultation services to teachers regarding the implementation of the independent learning Focus Group Discussion (FGD) policy and outreach regarding the implementation of quizizz media-based edutainment. Mentoring is carried out regularly once a month (running for 8 months). This assistance is carried out online via social media (Whatsapp Group) and offline, namely face to face. Evaluation and monitoring of activities. Evaluation and monitoring of activities is carried out periodically by involving implementing members and activity partners. Each evaluation stage will be carried out as a whole to determine the degree of success of the activity based on the targets that have been set. The results of the first stage evaluation will be used as a basis for implementation in the second year and beyond.